Pengembangan Multimedia Aksara Jawa Berbasis Kearifan Lokal Pada Siswa Kelas V Sekolah Dasar (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
This study aims to develop and test the effectiveness of Javanese script multimedia based on local wisdom. This multimedia was developed using the RnD research method with the ADDIE model. Data collection techniques used observation, interviews, and questionnaires. The data obtained were validated by material experts, media experts, teachers, response questionnaires, and assessment of reading Javanese script. The research subjects were 5th-grade students of SD Negeri Kesugihan. The data analysis technique used was inferential quantitative data analysis technique. The results are: (1) Javanese script multimedia products can be used as reference sources and media in learning, (2) the results of the feasibility test consist of: a) material expert validation gets 95.83% (very feasible), b) media experts validation got 91.1% (very decent), c) teacher practitioners score got 95.6% (very decent), d) students responses in a limited trial got 93.3% (very practical); students responses in the wide trial obtained 90% (very practical), e) the assessment of the ability to read Javanese script in the limited trial obtained 81.6% (good criteria) and in the broad trial obtained 82% (good) criteria. Multimedia Javanese script based on local wisdom is a solution for Javanese script learning’s problems in the technological era and can be used as a support in delivering learning materials in class.